2015
DOI: 10.1353/cpr.2015.0011
|View full text |Cite
|
Sign up to set email alerts
|

Somali Perspectives on Physical Activity: PhotoVoice to Address Barriers and Resources in San Diego

Abstract: Background Though many immigrants enter the U.S. with a healthy body weight, this health advantage disappears the longer they reside in the U.S. To better understand the complexities of obesity change within a cultural framework, a community-based participatory research (CBPR) approach, Photovoice, was utilized focusing on physical activity among Muslim Somali women. Objectives The CBPR partnership was formed to identify barriers and resources to engaging in physical activity with goals of advocacy and progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 22 publications
0
23
0
Order By: Relevance
“…Evidence on African immigrants and refugees in a mental health care setting shows that, by actively involving study participants, researchers are able to ensure meaningful and culturally appropriate scholarly work [ 216 ]. Similarly, Murray et al [ 217 ] found participant engagement in the research process positively influenced physical activity behaviour in East African communities in the United States; these engagements undoubtedly tap into communal agency, knowledge, and sense of belonging.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence on African immigrants and refugees in a mental health care setting shows that, by actively involving study participants, researchers are able to ensure meaningful and culturally appropriate scholarly work [ 216 ]. Similarly, Murray et al [ 217 ] found participant engagement in the research process positively influenced physical activity behaviour in East African communities in the United States; these engagements undoubtedly tap into communal agency, knowledge, and sense of belonging.…”
Section: Discussionmentioning
confidence: 99%
“…These characteristics, such as public spaces, safety, public transportation, or the role of urban architecture, have been identified previously as key environmental elements for the promotion of physical activity [8,38,39]. For instance, safety was identified as an emerging theme in Villaverde (low-SES neighborhood), which aligns with other Photovoice projects where residents of low-SES communities in San Diego identified safety as a barrier for physical activity [40]. We found some differences in the themes and discourses between both settings.…”
Section: Discussionmentioning
confidence: 77%
“…The use of photography reduces potential cultural, language, or literacy barriers (common in groups new to the US) to data collection and/or participation in research (Martin, Garcia and Leipert 2010). Photovoice has been used to examine the diets of immigrants to the United States, low-income families, and obese individuals varying in age (Van Oss et al 2014;Heidelberger & Smith 2015;Murray et al 2015;Turk, Fapohunda, and Zoucha 2014;Watts et al 2015). Its use across a variety of age groups and populations has reduced barriers and allowed researchers to collect lifestyle-related data.…”
Section: Introductionmentioning
confidence: 99%